Development of the Vietnamese Healthy Eating Index - Trijsburg, Laura; Van, Duong T. T.; Do, Ha T.P.; Kurotani, Kayo; Feskens, Edith J.M.; Talsma, Elise F. (Cambridge University Press, 2022)
Poor dietary quality is a major contributor to malnutrition and disease burden in Vietnam, necessitating the development of a tool for improving dietary quality. Food-based dietary guidelines (FBDGs) have been proposed to do this by providing specific, culturally appropriate and actionable recommendations. We developed the Vietnamese Healthy Eating Index (VHEI) to assess the adherence to the 2016–2020 Vietnamese FBDGs and the dietary quality of the general Vietnamese population. This VHEI consists of eight component scores, ‘grains’, ‘protein foods’, ‘vegetables’, ‘fruits’, ‘dairy’, ‘fats and oils’, ‘sugar and sweets’ and ‘salt and sauces’, representing the recommendations in the FBDGs. Each component score ranges from 0 to 10, resulting in a total VHEI score between 0 (lowest adherence) and 80 (highest adherence). The VHEI was calculated using dietary intake data from the Vietnamese General Nutrition Survey 2009–2010 (n = 8225 households). Associations of the VHEI with socio-demographic characteristics, energy and nutrient intakes and food group consumptions were examined. The results showed that the mean and standard deviation score of the VHEI was 43⋅3 ± 8⋅1. The component ‘sugar and sweets’ scored the highest (9⋅8 ± 1⋅1), whereas the component ‘dairy’ scored the lowest (0⋅6 ± 1⋅6). The intake of micronutrients was positively associated with the total VHEI, both before and after adjustment for energy intake. In conclusion, the VHEI is a valuable measure of dietary quality for the Vietnamese population regarding their adherence to the FBDGs.